2015
DOI: 10.1037/a0036316
|View full text |Cite
|
Sign up to set email alerts
|

Social reactions, self-blame, and problem drinking in adult sexual assault survivors.

Abstract: Objective The purpose of this study was to test a model of the relations of social reactions to sexual assault disclosure, self-blame and problem drinking. This is the first study to investigate whether type of self-blame has different relationships with social reactions and problem drinking in a large, diverse sample of sexually assaulted women. These relationships are important to investigate in order to identify specific targets for treatment and intervention with sexual assault victims and their social net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…There is also some evidence to suggest that shame is associated with adjustment among sexually victimized children and adolescents (Feiring, Taska & Lewis, ), although research in this population is limited. The communication of stigma to survivors via negative social reactions to SA disclosure prospectively predicts post‐traumatic stress symptomology in adults (Littleton, ; Ullman & Peter‐Hagene, ) and has been associated with depressive symptomology (Ahrens, Stansall, & Jennings, ; Orchowski, Untied, & Gidycz, ), problem drinking (Sigurvinsdottir & Ullman, ), anxiety (Orchowski et al., ), and health problems (Ahrens et al., ) in cross‐sectional studies of adults. Qualitative research with adolescent SA survivors also suggests that negative and positive social reactions are influential to their emotional well‐being (e.g., survivors report that being blamed by the police led them to feel angry and blame themselves; Greeson, Campbell, & Fehler‐Cabral, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence to suggest that shame is associated with adjustment among sexually victimized children and adolescents (Feiring, Taska & Lewis, ), although research in this population is limited. The communication of stigma to survivors via negative social reactions to SA disclosure prospectively predicts post‐traumatic stress symptomology in adults (Littleton, ; Ullman & Peter‐Hagene, ) and has been associated with depressive symptomology (Ahrens, Stansall, & Jennings, ; Orchowski, Untied, & Gidycz, ), problem drinking (Sigurvinsdottir & Ullman, ), anxiety (Orchowski et al., ), and health problems (Ahrens et al., ) in cross‐sectional studies of adults. Qualitative research with adolescent SA survivors also suggests that negative and positive social reactions are influential to their emotional well‐being (e.g., survivors report that being blamed by the police led them to feel angry and blame themselves; Greeson, Campbell, & Fehler‐Cabral, ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional community study also showed that victims who were drinking prior to the assault reported greater self-blame for the assault than nondrinking victims (Ullman & Najdowski, 2010). In turn, self-blame is related to more psychological distress and risk of revictimization (Breitenbecher, 2006; Miller, Markman, & Handley, 2007), and certain types of self-blame attributions mediated the effect of negative social reactions on problem drinking (Sigurvinsdottir & Ullman, 2015). …”
mentioning
confidence: 99%
“…Although both behavioral and characterological self-blame have been associated with poorer adjustment, most researchers agree that characterological self-blame attributions have stronger negative effects (Breitenbecher, 2006; Frazier, 2003; Koss et al, 2002; Littleton & Breitkopf, 2006; Sigurvinsdottir & Ullman, 2015). Thus, not all types of self-blame attributions can be expected to affect PTSD symptomatology in the same way.…”
mentioning
confidence: 99%
“…Even for victims who had begged the assailant to stop, assault by an acquaintance resulted in self-blame and minimizing the experience (Edwards et al, 2014). Those who experienced negative judgment were even more likely to blame themselves and increase their alcohol consumption following the assault (Jones et al 2009;Sigurvinsdottir & Ullman, 2014). Self-blame impairs psychological healing (Miller, Handley, Markman & Miller, 2010); and minimizing the assault can contribute to future victimization (Edwards et al, 2014).…”
Section: Impact Of Substance Use On Sexual Assaultmentioning
confidence: 99%